Steroid therapy and outcome of parapneumonic pleural effusions (STOPPE): study protocol for a multicenter, double-blinded, placebo-controlled randomized clinical trial - Fitzgerald, D; Waterer, G; Read, C; Fysh, E; Shrestha, R; Stanley, C; Muruganandan, S; Lan, N; Popowicz, N; Peddle-Mcintyre, C; Rahman, N; Gan, S; et al. (Wolters Kluwers Health, Inc., 2019)
Background: Community-acquired pneumonia (CAP) is a major global disease. Parapneumonic effusions often complicate CAP and range from uninfected (simple) to infected (complicated) parapneumonic effusions and empyema (pus). CAP patients who have a pleural effusion at presentation are more likely to require hospitalization, have a longer length of stay and higher mortality than those without an effusion. Conventional management of pleural infection, with antibiotics and chest tube drainage, fails in about 30% of cases. Several randomized controlled trials (RCT) have evaluated the use of corticosteroids in CAP and demonstrated some potential benefits. Importantly, steroid use in pneumonia has an acceptable safety profile with no adverse impact on mortality. A RCT focused on pediatric patients with pneumonia and a parapneumonic effusion demonstrated shorter time to recovery. The effects of corticosteroid use on clinical outcomes in adults with parapneumonic effusions have not been tested. We hypothesize that parapneumonic effusions develop from an exaggerated pleural inflammatory response. Treatment with systemic steroids may dampen the inflammation and lead to improved clinical outcomes. The steroid therapy and outcome of parapneumonic pleural effusions (STOPPE) trial will assess the efficacy and safety of systemic corticosteroid as an adjunct therapy in adult patients with CAP and pleural effusions. Methods: STOPPE is a pilot multicenter, double-blinded, placebo-controlled RCT that will randomize 80 patients with parapneumonic effusions (2:1) to intravenous dexamethasone or placebo, administered twice daily for 48 hours. This exploratory study will capture a wide range of clinically relevant endpoints which have been used in clinical trials of pneumonia and/or pleural infection; including, but not limited to: time to clinical stability, inflammatory markers, quality of life, length of hospital stay, proportion of patients requiring escalation of care (thoracostomy or thoracoscopy), and mortality. Safety will be assessed by monitoring for the incidence of adverse events during the study. Discussion: STOPPE is the first trial to assess the efficacy and safety profile of systemic corticosteroids in adults with CAP and pleural effusions. This will inform future studies on feasibility and appropriate trial endpoints. Trial registration: ACTRN12618000947202 Protocol version: version 3.00/26.07.18.